Regio- and Diastereoselective Cycloaddition of Azomethine Ylides with Benzylidenemalononitrile: Assembly of a New Set of Multisubstituted 4,4-Dicyanopyrrolidine-2-carboxylate and Nornicotine Scaffolds - Rajkumar, Vadla; Babu, Srinivasarao Arulananda (Synlett, 2014)
Regio- and diastereoselective 1,3-dipolar cycloaddition reaction of azomethine ylides derived from N-benzylideneiminoglycinates in the presence of catalytic quantities of silver salts with benzylidenemalononitriles (Knöevenagel adducts) is reported. The reaction of azomethine ylides with benzylidenemalononitriles gave a new class of 3,5-aryl/heteroaryl-substituted 4,4-dicyanopyrrolidine-2-carboxylate (proline) and nornicotine scaffolds having three stereocenters, with very good diastereoselectivity. The stereochemistry of representative major diastereomers was confirmed by single crystal X-ray structure analyses.
Keywords: 1,3-dipolar cycloaddition; pyrrolidine; regioselectivity; stereoselective synthesis; ylides